PENERAPAN MEDIA PEMBELAJARAN GEOGRAFI BERBASIS SPATIAL.IO UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X DI SMAN 1 BATIPUH - Permata Sari , Ira; Mariya, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the application and effectiveness of Spatial.io-based geography learning media in improving critical thinking skills of grade X students at SMAN 1 Batipuh. Critical thinking skills refer to critical thinking indicators quoted from Bagas, namely: interpretation, analysis, evaluation, conclusions, explanations, self-regulation. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research subjects consisted of an experimental class and a control class. Data collection techniques were carried out through critical thinking ability tests in the form of pre-tests and post-tests. Data were analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results showed that students' critical thinking skills in the experimental class experienced a higher increase than the control class. It can be concluded that the application of Spatial.io-based learning media is effective in improving students' critical thinking skills and supporting the creation of innovative geography learning.